2022
DOI: 10.1039/d2tb00074a
|View full text |Cite
|
Sign up to set email alerts
|

EGCG-crosslinked carboxymethyl chitosan-based hydrogels with inherent desired functions for full-thickness skin wound healing

Abstract: Hydrogel wound dressings have attracted intense and increasing interest for their extracellular matrix like property and bioactive material delivery ability. Various functional hydrogels loading metals (and their oxides), antibiotics and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…EGCG can prolong the lifespan by inducing mitochondrial reactions 107 . EGCG cross-linked in chitosan hydrogels has been shown to promote proliferation and remodeling processes, such as regeneration of the epidermis, dermis, and skin attachments, to accelerate skin wound healing 108 . EGCG shows neuroprotective effects in Alzheimer's disease and other neurodegenerative disorders by reducing A β its expression and inflammatory responses 109 , 110 .…”
Section: Natural Products In the Treatment Of Inflammatory Diseases A...mentioning
confidence: 99%
“…EGCG can prolong the lifespan by inducing mitochondrial reactions 107 . EGCG cross-linked in chitosan hydrogels has been shown to promote proliferation and remodeling processes, such as regeneration of the epidermis, dermis, and skin attachments, to accelerate skin wound healing 108 . EGCG shows neuroprotective effects in Alzheimer's disease and other neurodegenerative disorders by reducing A β its expression and inflammatory responses 109 , 110 .…”
Section: Natural Products In the Treatment Of Inflammatory Diseases A...mentioning
confidence: 99%
“…The peaks at 7.95–7.56 ppm were attributed to phenyl protons of QP and those at 4.35–3.24 ppm were ascribed to the C2–C6 protons of CMCS glycan units. [ 26 ] Based on the integration area, the QP substitution degree was ≈16.6% (Figure 1f). Notably, adjusting the QP/CMCS feeding ratio from 0.2 to 2.0 changed the QP substitution degree from 5.6% to 16.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The wound closure rate on day 7 was used as an evaluation index in a mouse full-thickness wound model. We discussed and compared the different functional characteristics of the dressings such as Sr-doped BGN (BSr@PPE), quaternized chitosan/graphene oxide fabricated hydrogel (QCS-CD-AD/GO), poly(citrate-glycol-siloxane)/F127-ε-poly- l -lysine hybrid hydrogel (FEPCGS), Eu 2 O 3 nanorods reinforced hydrogel (FHAE), photo-crosslinked CeO 2 hydrogel and EGCG-crosslinked chitosan hydrogel (EP) [ [51] , [52] , [53] , [54] , [55] , [56] ]. These results indicated that BGN@PTE provided significantly better wound healing performance than single antioxidant or angiogenic dressings ( Fig.…”
Section: Resultsmentioning
confidence: 99%